2015
DOI: 10.1021/acs.biomac.5b00229
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Inhibition by Curcumin in Cancer Cells: A Dual Mode of Action

Abstract: Epidermal Growth Factor Receptor (EGFR) is an important target of anticancer therapy. Nowadays, the search for new molecules inhibiting this receptor is turning toward natural substances. One of the most promising natural compounds that have shown an anti-EGFR activity is curcumin, a polyphenol found in turmeric. Its effect on the receptor kinase activity and on the receptor autophosphorylation has been already described, but the mechanism of how curcumin interacts with EGFR is not fully elucidated. We demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 77 publications
2
45
0
Order By: Relevance
“…Mitochondrial membrane potential was decreased, the release of cytochrome c into the cytosol was induced, and then caspase-9 and caspase-3 were activated [34]. Besides, curcumin inhibited the enzymatic activity of the epidermal growth factor receptor (EGFR) intracellular domain, and also influenced the cell membrane environment of EGFR, which was involved in the growth of lung cancer [35]. According to another study, the crosstalk between adherens’ junctions and Wnt signaling pathways was regulated by early growth response 1 (EGR-1), suggesting that EGR-1 might regulate cell proliferation and migration, which was confirmed in vitro.…”
Section: Turmeric and Curcuminmentioning
confidence: 99%
“…Mitochondrial membrane potential was decreased, the release of cytochrome c into the cytosol was induced, and then caspase-9 and caspase-3 were activated [34]. Besides, curcumin inhibited the enzymatic activity of the epidermal growth factor receptor (EGFR) intracellular domain, and also influenced the cell membrane environment of EGFR, which was involved in the growth of lung cancer [35]. According to another study, the crosstalk between adherens’ junctions and Wnt signaling pathways was regulated by early growth response 1 (EGR-1), suggesting that EGR-1 might regulate cell proliferation and migration, which was confirmed in vitro.…”
Section: Turmeric and Curcuminmentioning
confidence: 99%
“…Likewise, Zhu et al [39] reported that curcumin suppressed lung cancer stem cells via inhibiting Wnt/beta-catenin and sonic hedgehog pathways. Intriguingly, a recent study presented by Starok et al [40] demonstrated that insertion of curcumin into lipid bilayer influenced the cell membrane environment and interfered with EGFR signalling as well. Curcumin has also been revealed with promising results against the glioblastoma multiforme while in combination with cytotoxic chemotherapy agents.…”
Section: Discussionmentioning
confidence: 99%
“…reported that curcumin suppressed lung cancer stem cells via inhibiting Wnt/beta‐catenin and sonic hedgehog pathways. Intriguingly, a recent study presented by Starok et al . demonstrated that insertion of curcumin into lipid bilayer influenced the cell membrane environment and interfered with EGFR signalling as well.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of EGF receptor is represented by an extracellular ligand-binding domain, a single transmembrane region with hydrophobic characteristics, and an intracellular module including the tyrosine kinase domain [75]. …”
Section: Cell Proliferationmentioning
confidence: 99%
“…Curcumin was able to inhibit EGFR tyrosine kinase in a concentration of 1 μM after 4 h of cell exposoure. The exact molecular mechanism of this short-term inhibition remains unknown [75]. …”
Section: Cell Proliferationmentioning
confidence: 99%